2015
DOI: 10.1002/star.201500155
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metal ions in water by starch esters

Abstract: Corn starch has been modified with naturally occurring compounds, maleic acid (MA) and itaconic acid (IA), by esterification in an aqueous medium catalyzed by NaOH to produce adsorbents for heavy metals removal in water. The ester formation has been confirmed by wide angle x-ray scattering (WAXS), thermogravimetric analysis (TGA), Fourier Transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). The effect of the mono and di-substitution with both acids, on the solubility and the swelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…In general, the ability of adsorbent materials to bind metal cations depends on factors such as the ionic charge, electronegativity, and ionic radius of hydration of the metal, as well as the characteristics of the adsorbent. Unmodified starch can bind small amounts of metals by physical entrapment and weak electrostatic interactions . By grafting carboxylic groups onto the backbone of starch, it is expected to increase the strength of the attractive forces between the hydrogels and copper cations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the ability of adsorbent materials to bind metal cations depends on factors such as the ionic charge, electronegativity, and ionic radius of hydration of the metal, as well as the characteristics of the adsorbent. Unmodified starch can bind small amounts of metals by physical entrapment and weak electrostatic interactions . By grafting carboxylic groups onto the backbone of starch, it is expected to increase the strength of the attractive forces between the hydrogels and copper cations.…”
Section: Resultsmentioning
confidence: 99%
“…IA is an unsaturated dicarboxylic acid produced via the fermentation of carbohydrates with fungi . The research group of Soto et al has produced starch‐IA esters and hydrogels, and evaluated their potential for removal of metals from wastewater. However, the effect of the chains’ structure of starch has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The modified and native starches showed reasonable adsorption capacity for all the investigated cations. It was shown that the native starch did not exhibit selectivity for any of the cations, whereas the itaconate starches removed higher content of Pb +2 with the lowest hydration radius in comparison with other ions [64]. The structural formulae of the prepared esters are given below in Figure 9.…”
Section: Maleate Starch Semi-ester Maleate Starch Di-estermentioning
confidence: 99%
“…Starch is naturally able to bind metal ions, mainly by the processes of physical entrapment along with minor electrostatic interactions . By incorporating carboxyl groups via the grafting of CA and IA, it was expected to increase the adsorption capacity.…”
Section: Resultsmentioning
confidence: 99%
“…[63][64][65] Starch is naturally able to bind metal ions, mainly by the processes of physical entrapment along with minor electrostatic interactions. [66] By incorporating carboxyl groups via the grafting of CA and IA, it was expected to increase the adsorption capacity. The grafting of carboxyl groups onto starch has been shown to increase its ion exchange capacity due to the enhanced electrostatic interactions between the adsorbent and the adsorbate.…”
Section: Heavy Metal Adsorptionmentioning
confidence: 99%